Symphony No. 9 in E Minor, Op. 95 From the New World - Dvořák, Antonín Leopold. 1841-1904 (Colección Dover Miniature Scores, 1997)
A great and lasting favourite in the vast symphonic literature, Dvorak's New World Symphony is among the composer's most enduring and appealing works ever since its premiere in 1893. This work appears in full score with original instrumentation and bar numbered movements. Ideal for study purpose.